Microbes in cahoots with plants: MIST to hit the jackpot of agricultural productivity during drought - Kaushal, M. (MDPI, 2019)
Drought conditions marked by water deficit impede plant growth thus causing recurrent decline in agricultural productivity. Presently, research efforts are focussed towards harnessing the potential of microbes to enhance crop production during drought. Microbial communities, such as arbuscular mycorrhizal fungi (AMF) and plant growth-promoting rhizobacteria (PGPR) buddy up with plants to boost crop productivity during drought via microbial induced systemic tolerance (MIST). The present review summarizes MIST mechanisms during drought comprised of modulation in phytohormonal profiles, sturdy antioxidant defence, osmotic grapnel, bacterial exopolysaccharides (EPS) or AMF glomalin production, volatile organic compounds (VOCs), expression of fungal aquaporins and stress responsive genes, which alters various physiological processes such as hydraulic conductance, transpiration rate, stomatal conductivity and photosynthesis in host plants. Molecular studies have revealed microbial induced differential expression of various genes such as ERD15 (Early Response to Dehydration 15), RAB18 (ABA-responsive gene) in Arabidopsis, COX1 (regulates energy and carbohydrate metabolism), PKDP (protein kinase), AP2-EREBP (stress responsive pathway), Hsp20, bZIP1 and COC1 (chaperones in ABA signalling) in Pseudomonas fluorescens treated rice, LbKT1, LbSKOR (encoding potassium channels) in Lycium, PtYUC3 and PtYUC8 (IAA biosynthesis) in AMF inoculated Poncirus, ADC, AIH, CPA, SPDS, SPMS and SAMDC (polyamine biosynthesis) in PGPR inoculated Arabidopsis, 14-3-3 genes (TFT1-TFT12 genes in ABA signalling pathways) in AMF treated Solanum, ACO, ACS (ethylene biosynthesis), jasmonate MYC2 gene in chick pea, PR1 (SA regulated gene), pdf1.2 (JA marker genes) and VSP1 (ethylene-response gene) in Pseudomonas treated Arabidopsis plants. Moreover, the key role of miRNAs in MIST has also been recorded in Pseudomonas putida RA treated chick pea plants.